MANAGEMENT OF HYPERTENSION IN RURAL AREA OF NORTH-EASTERN REGION OF THE MAHARASHTRA: A INTERVENTIONAL STUDY - Kotecha , Raunak; Mahajan , Gaurav; Hadke, Saurabh; Ambad, Ranjit Sidram (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension being major chronic and non-communicable, leads to heart failure, coronary artery disease, stroke, impairment of kidney function, disability, and early death. Lifestyle behaviours such as unhealthy diet, increased salt intake, physical inactivity, use of tobacco and alcohol abuse are principal risk factor which leads to development of hypertension.Study was randomised, community-based health and knowledge trial was conducted in rural area around ABV rural hospital, Wardha. The study was approved by research and ethics board of DMIMISU Sawangi Meghe.In present study total 180 patients agreed to participate they were divided into 3 groups randomly. Following steps were taken to avoid selection bias during random allocation. Group was randomised only after baseline survey; An epidemiologist who was not in contact with study randomised the groups. Group 1 (self-reading and learning, n=60) participants received orientation on reading materials to learn knowledge on hypertension through the poster, messages and pamphlet and health education booklets monthly. Group 2 (training and health education, n=60) participated in training and health education, health education consisted of 30 min lecture per month. Group 3(interactive education workshop, n=60) workshop on knowledge about hypertension was given using visual health education (cartoons, animals, food models, salt spoons, and CVD models)At the baseline, most participants (about 2/3) did not regularly take BP lowering medications. After the 12monts of health education intervention, there were statistically significant increases in hypertension-related knowledge scores in all the three intervention groups. However, the increase was significantly greater in the interactive education workshop group 3 (mean score increased from 3.1 to 7.9) than in the regular lecture group 2 (mean score increased from 3.1 to 6.9) or self-learning reading group 1 (mean score increased from 3.9 to 6.1). Regular use of medications for hypertension and regular physical activity were significantly more frequent after the intervention in all the three groups, but the improvements were progressively greater from group 1 to group 2 to Group 3. There were no significant differences in smoking and alcohol use at both the baseline or after the intervention among the three groups.In end, interactive education workshops possibly will be the most effective approach in community-based health education programs for hypertensive patients in improving patients’ knowledge on hypertension and lessening clinical risk factors for inhibiting hypertension-related problems.